An engineered ClyA nanopore detects folded target proteins by selective external association and pore entry. - Soskine, M; Biesemans, A; Moeyaert, B; Cheley, S; Bayley, H; Maglia, G (2012)
Nanopores have been used in label-free single-molecule studies, including investigations of chemical reactions, nucleic acid analysis, and applications in sensing. Biological nanopores generally perform better than artificial nanopores as sensors, but they have disadvantages including a fixed diameter. Here we introduce a biological nanopore ClyA that is wide enough to sample and distinguish large analyte proteins, which enter the pore lumen. Remarkably, human and bovine thrombins, despite 86% sequence identity, elicit characteristic ionic current blockades, which at -50 mV differ in their main current levels by 26 ± 1 pA. The use of DNA aptamers or hirudin as ligands further distinguished the protein analytes. Finally, we constructed ClyA nanopores decorated with covalently attached aptamers. These nanopores selectively captured and internalized cognate protein analytes but excluded noncognate analytes, in a process that resembles transport by nuclear pores.